Utilization of coconut flour in chips - Bantol, Maria Gracia Hamili; Francisco, Ma. Leonora dL. (1998)
Coconut chips were developed for the purpose of increasing the utilization of coconut flour and for improving the nutritional quality of snack chips available in the market. Variables studied were levels of coconut flour to be incorporated into the chips and type of flavoring to mask the coconut flavor. Incorporation of coconut flour varied from 20, 30, and 40% while flavorings evaluated were adobo and barbecue flavors. Subjective evaluation was made to determine the effects of the incorporation of coconut flour and flavors. Objective analysis on the other hand was done to determine proximate composition of the most acceptable product. Results of sensory evaluation indicated that the maximum amount of coconut flour that can be incorporated into the production of chips was 30% and adobo flavored coconut chips were better than barbecue flavored and natural flavored coconut chips. Proximate analysis showed that the sample contained large amounts of carbohydrates and fat. Hence, further studies still need to be done to better improve the palatability and nutritional value of this product.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut flour